2008
DOI: 10.1371/journal.pone.0002003
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Injury in Chronic Pancreatitis: Decoding the Role of the High-Risk SPINK1 N34S Haplotype Using Meta-Analysis

Abstract: BackgroundThe complex interactions between recurrent trypsin-mediated pancreatic injury, alcohol-associated pancreatic injury and SPINK1 polymorphisms in chronic pancreatitis (CP) are undefined. We hypothesize that CP occurs as a result of multiple pathological mechanisms (pathways) that are initiated by different metabolic or environmental factors (etiologies) and may be influenced differentially by downstream genetic risk factors. We tested this hypothesis by evaluating the differences in effect size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 65 publications
(67 reference statements)
2
84
0
2
Order By: Relevance
“…The following studies have shown that mutations in the SPINK1 gene are associated with CP of various etiologies including idiopathic, familial, and tropical (Witt et al 2000;Pfützer et al 2000;Chen et al 2001;Bhatia et al 2002;Kume et al 2005;Aoun et al 2008). The p.N34S mutation has been found worldwide in CP patients and healthy controls, with an average allele frequency of 9.7% and 1%, respectively (Witt et al 2000;Pfützer et al 2000;Chen et al 2001;Bhatia et al 2002;Kume et al 2005;Aoun et al 2008). In addition to CP, we and others have reported that the p.N34S mutation is strongly associated with recurrent acute pancreatitis, but does not increase the risk of the first or sentinel acute pancreatitis event (Aoun et al 2010;Masamune et al 2011).…”
Section: Spink1 Mutationsmentioning
confidence: 99%
“…The following studies have shown that mutations in the SPINK1 gene are associated with CP of various etiologies including idiopathic, familial, and tropical (Witt et al 2000;Pfützer et al 2000;Chen et al 2001;Bhatia et al 2002;Kume et al 2005;Aoun et al 2008). The p.N34S mutation has been found worldwide in CP patients and healthy controls, with an average allele frequency of 9.7% and 1%, respectively (Witt et al 2000;Pfützer et al 2000;Chen et al 2001;Bhatia et al 2002;Kume et al 2005;Aoun et al 2008). In addition to CP, we and others have reported that the p.N34S mutation is strongly associated with recurrent acute pancreatitis, but does not increase the risk of the first or sentinel acute pancreatitis event (Aoun et al 2010;Masamune et al 2011).…”
Section: Spink1 Mutationsmentioning
confidence: 99%
“…Наличие мутации N34S определяет низкий риск развития любой этиологии ХП, умеренный риск токсического ХП, высокий риск идиопатического ХП; низкий риск ранней клинической манифестации ХП любой этиологии, умеренный риск для токсического ХП, высокий риск -для идиопатического ХП. Полученные нами данные условно укладываются в наиболее доказательные результаты крупного метаанализа 24 исследований, включающих 2421 случай ХП (и 4857 контроль), свидетельствующие о высоком риске развития ХП у носителей мутации N34S -ОШ развития ХП достигает 11,00 (95% доверительный интервал (ДИ) 7,59-15,93), а для идиопатического ХП еще выше -14,97 (95% ДИ 9,09-24,67) [30].…”
Section: рисunclassified
“…Наиболее специфичной оказалась группа идиопатического ХП, в которой отмечена максимальная частота данной мутации, наиболее тяжелое и осложненное течение ХП, больший риск неблагоприятных исходов. Хотя роль мутаций гена ПИТ в развитии ХП была оценена в нескольких западных исследованиях [12][13][14][15]30], наше исследование -первое, в котором была изучена частота мутации N34S у больных ХП в Москве и Московской области, и пока единственное в России, в котором удалось доказать, что данная мутация играет существенную роль в развитии, по крайней мере, токсических и идиопатических панкреатитов.…”
Section: рисunclassified
“…Serine protease inhibitor Kazal type 1 (SPINK1) provides the first line of defense against prematurely activated trypsinogen by physically blocking the active site of trypsin (Rinderknecht 1986;Witt et al 2000). Mutations in the SPINK1 gene are thought to diminish the protection against prematurely activated trypsin, and are thereby linked to trypsin-related pancreatic injury (Pfützer et al 2000;Witt et al 2000;Chen et al 2001;Bhatia et al 2002;Kume et al 2005Kume et al , 2006Aoun et al 2008).…”
mentioning
confidence: 99%
“…Previous studies have shown that mutations in the SPINK1 gene are associated with CP of various forms including idiopathic, familial, and tropical (Pfützer et al 2000;Witt et al 2000;Chen et al 2001;Bhatia et al 2002;Kume et al 2005Kume et al , 2006Aoun et al 2008). The p.N34S (c.101A>G) mutation has been found worldwide in CP patients and healthy controls, with an average allele frequency of 9.7% and 1%, respectively (Pfützer et al 2000;Witt et al 2000;Aoun et al 2008;Kereszturi et al 2009).…”
mentioning
confidence: 99%